Quorum sensing and quorum quenching in selected bacteria isolated from diseased tilapia fish / Chan Xin Yue - Chan, Xin Yue (2013)
Living in a polymicrobial community, bacteria communicate within and among species for interaction. This cell-cell communication in bacteria is termed quorum sensing (QS). Among the QS signaling molecules, N˗acyl homoserine lactone (AHL) is one of the well characterized QS signaling molecules produced and used by vast group of Proteobacteria. This QS signaling molecule often associated with coordinating certain group behavior of bacteria such as the bioluminescence, biofilm formation and regulation of virulence factors expression. On the other hand, other than production, some bacteria also degrade the QS signaling molecules and this is termed as quorum quenching (QQ). It is believed that the bacteria possessed QQ as a strategy to survive in the competitive environment against the QS bacteria. In these studies, five bacteria are isolated from diseased tilapia fish namely Bacillus sp. strain W2.2, Klebsiella oxytoca strain W4.2, Pseudomonas sp. strain W3, Pseudomonas aeruginosa strain W3.1 and Serratia marcescens sp. strain W2.3. The QS signaling molecules produced by these bacteria are characterized by thin layer chromatography (TLC) and liquid chromatography mass spectrophotometry (LCMS). Results showed that P. aeruginosa strain W3.1 produces a wide range of Pseudomonas quinolone signaling (PQS), and AHLs including unusually long-chain N-(3-oxohexadecanoyl)-L-homoserine lactone (OC16-HSL), but none of these compounds are detected from Pseudomonas sp. strain W3. In contrast, Pseudomonas sp. strain W3 degraded N-butanoyl-L-homoserine lactone (C4-HSL) and N-hexanoyl-L-homoserine lactone (C6-HSL). N-dodecanoyl-L-homoserine lactone (C12-HSL) was detected from spent supernatant from S. marcescens strain W2.3 and this is the first report stating long chain AHL produced by Serratia sp.. Bioassay using skimmed milk agar has confirmed that with the exception of Klebsiella sp. strain W4.2, all isolates showed proteolytic activity, while assays using sheep blood agar showed that Bacillus sp. strain W2.2 and Pseudomonas sp. strains W3 and P. aeruginosa strain W3.1 have hemolytic activity.